Development of a method for evaluation of absorbed doses in preclinical in vivo μcT - Deyhle, Richard T.; Bernhardsson, Christian ; 0000-0002-6577-7473; Olsson, Lars E. ; 0000-0001-6090-6697; Sydoff, Marie (Radiation Protection Dosimetry, 2025)
In vivo preclinical X-ray micro-computed tomography (μCT) imaging is widely used to obtain three-dimensional anatomical information of small animals. However, the potential for radiation exposure to influence experimental outcomes necessitates accurate dose estimation. The aim of this study was to develop a robust and reproducible method for estimating and evaluating absorbed doses in small animals undergoing preclinical in vivo μCT imaging. Absorbed doses were measured at four separate positions within a dedicated polymethyl methacrylate phantom using MCP-N (LiF, Cu, P) thermoluminescence dosemeters (TLDs) and a novel type of optically stimulated luminescence dosemeter (OSLD) made from household salt (NaCl). The findings were benchmarked against the vendor's absorbed dose estimates, revealing a discrepancy between the measured and provided values. The results for the OSLDs followed a similar trend to the TLDs, though significant statistical differences were found between the luminescent dosemeters and the vendor values. In this study, a method for measuring the absorbed doses from μCT systems was presented. The results indicate a need for thorough dose measurements prior to performing longitudinal imaging studies.